Digital ethnography : anthropology, narrative, and new media. - Underberg, Natalie M. (Universitu of Texas Press, 2014)
"Digital ethnography can be understood as a method for representing real-life cultures through storytelling in digital media. Enabling audiences to go beyond absorbing facts, computer-based storytelling allows for immersion in the experience of another culture. A guide for anyone in the social sciences who seeks to enrich ethnographic techniques, Digital Ethnography offers a groundbreaking approach that utilizes interactive components to simulate cultural narratives. Integrating insights from cultural anthropology, folklore, digital humanities, and digital heritage studies, this work brims with case studies that provide in-depth discussions of applied projects. Web links to multimedia examples are included as well, including projects, design documents, and other relevant materials related to the planning and execution of digital ethnography projects. In addition, new media tools such as database development and XML coding are explored and explained, bridging the literature on cyber-ethnography with inspiring examples such as blending cultural heritage with computer games. One of the few books in its field to address the digital divide among researchers, Digital Ethnography guides readers through the extraordinary potential for enrichment offered by technological resources, far from restricting research to quantitative methods usually associated with technology. The authors powerfully remind us that the study of culture is as much about affective traits of feeling and sensing as it is about cognition--an approach facilitated (not hindered) by the digital age."--Publisher's website.